Bone marrow levels of 25 hydroxy vitamin D are not depressed in cases of hip fracture compared with controls. (27th December 2013) - Power, J.; Taggart, J.; Parker, M.; Berry, J. L.; Reeve, J.
<x xml:space="preserve">Abstract</x> There is little information on tissue as distinct from plasma levels of vitamin D metabolites in cases of hip fracture compared with controls. Femoral neck fractures in the elderly are associated with increased cortical remodelling and endosteal resorption, leading to regional increases in porosity and reduced cortical thickness. Vitamin D metabolites play a central role in the maintenance of normal serum calcium levels and may, through interactions with parathyroid hormone, exert an important influence on bone structure. To investigate whether hip fracture might be associated with tissue vitamin D deficiency, we have measured by radioimmunoassay the levels of 25 hydroxy vitamin D (25 (OH)D) in bone marrow samples extracted from the proximal femurs of 16 female subjects who had suffered fracture (mean age = 82.1 years, standard error (se) 1.9) and nine sex matched post mortem controls (mean age = 83.8 years, se 2.5). Twenty five (OH)D concentrations were significantly greater in the fracture cases (median = 3.7, IQR = 2.5–3.9 ng/g) than in the control group (median = 1.5, IQR = 0.9–2.3 ng/g; P = 0.0007, non‐parametric Wilcoxon/Kruskal–Wallis test). It was suggested in the 1970s that bone loss and hip fracture risk in the UK were driven by vitamin D deficiency. Our results suggest that the alterations in femoral neck bone microstructure and remodelling in hip fracture cannot be assigned to the single cause of relative deficiency of vitamin D. Vitamin D deficiency or insufficiency may nevertheless increase remodelling and loss of bone tissue and contribute causally to a minority of hip fractures. Copyright © 2013 John Wiley & Sons, Ltd.